Water use efficiency by coffee arabica after glyphosate application - Carvalho, Felipe Paolinelli de; França, André Cabral; Souza, Bruna Pereira; Fialho, Cíntia Teixeira; Santos, José Barbosa; Silva, Antonio Alberto (Acta Scientiarum. Agronomy, 2014)
Many coffee growers apply glyphosate in directed applications, but some phytotoxicity has been noted. It is believed some herbicides can exert a direct or indirect negative effect on photosynthesis by reducing the metabolic rate in a way that can affect the water use efficiency. The objective of this study was to investigate the variables related to water use among coffee cultivars subjected to the application of glyphosate and the effects of each dose. The experiment was conducted in a greenhouse using three varieties of coffee (Coffea arabica), Acaiá (MG-6851), Catucaí Amarelo (2SL) and Topázio (MG-1190), and three doses of glyphosate (0.0, 115.2 and 460.8 g acid equivalent ha-1), in a factorial 3 x 3 design. At 15 days after application, a reduction in stomatal conductance was observed, and smaller transpiration rate and water use efficiency were found in the fourth leaf at 15 days after application. There was a decrease in the transpiration rate at 45 DAA, with the Acaiá cultivar showing reductions with 115.2 g ha-1. There was transitory reduction in water use efficiency with glyphosate application, but can affect the growth and production. The Acaiá cultivar showed the highest tolerance to glyphosate because the water use efficiency after herbicide application.